Bioarchaeology and identity revisited - Knudson, Kelly J.; Stojanowski, Christopher M. (Christopher Michael), 1973-; Larsen, Clark Spencer (Bioarchaeological interpretations of the human past., 2020)
"This volume highlights new directions in the study of social identities in past populations. Contributors expand the scope of the field regionally, methodically, and theoretically, moving behind the previous focus on single aspects of identity by demonstrating multi-scalar approaches and by explicitly addressing intersectionality in the archaeological record"--